Iodine Intake from Universal Salt Iodization Programs and Hashimoto’s Thyroiditis: A Systematic Review - Hernando Vargas-Uricoechea; Alejandro Castellanos-Pinedo; Ivonne A. Meza-Cabrera; María V. Pinzón-Fernández; Karen Urrego-Noguera; Hernando Vargas-Sierra (Diseases)
Background: Hashimoto’s thyroiditis (HT) is characterized by the loss of tolerance to thyroid autoantigens [thyroid peroxidase (TPO) and thyroglobulin (Tg)], usually identifying circulating antibodies (Abs) against these thyroid autoantigens (TPOAb and/or TgAb), together with a significant lymphocytic infiltration, causing an increased risk of hypothyroidism. Among the multiple mechanisms described for the development of HT is the nutritional status of several micronutrients, including iodine. Iodine deficiency or excess is associated with thyroid function disorders and, likely, thyroid autoimmunity. Thus, iodized salt intake [especially through universal salt iodization (USI) programs] may be influencing the prevalence of HT. The objectives of this systematic review are to describe and analyze changes over time in the prevalence of HT following the implementation of USI programs. Methods and results: The following databases were consulted for articles published from January 1965 to January 2025: Pubmed/Medline; ProQuest; Scopus; Biosis; Web of Science; and Google Scholar. The search terms were as follows: “iodine”, “salt”, “intake”, “prevalence”, AND Hashimoto’s thyroiditis. Only English language articles were taken into account, and each of them was scrutinized according to the JBI Critical Appraisal Checklist. Only those studies in which the design, study population, number of participants, country, evaluation post-USI (years), and the prevalence of thyroid Abs positivity were described were included. In total, 74 studies were identified, of which 31 evaluated thyroid Abs values post-USI. Conclusions: Excess iodine intake, mediated by USI programs without an adequate follow-up and monitoring plan, may explain (at least in part) the prevalence and distribution of HT; therefore, it is a real challenge to establish a balance between healthy salt intake, USI program strategies, and possible functional outcomes and thyroid autoimmunity in the population. Registration number: INPLASY202540074.